Middle-Late Holocene palynology and marine mollusks from Archipiélago Cormoranes area, Beagle Channel, southern Tierra del Fuego, Argentina - Candel, Maria Soledad (2009)
The palynology and marine mollusks of a marine sequence from Río Ovando (54° 51′ S, 68° 35′ W), Archipiélago Cormoranes, Beagle Channel, has been studied in order to reconstruct paleoenvironmental conditions during the Middle-Late Holocene. The dinoflagellate cyst assemblages from Río Ovando sequence reflect fjord (estuarine) environments close to terrestrial ice field, affected by glacier meltwater discharge, and characterized by short-term oscillations of sea-surface water parameters. The base of the section, which is dated at about ca. 4160 14C yr B.P. (4736 cal yr B.P.) (Palynological Subzone RO-2c), is characterized by a high species diversity of dinocyst and mollusks, and it is immediately followed by an interval (Palynological Subzone RO-2b) characterized by the presence of the Echinidinium-Islandinium complex and the monospecific Mytilus mollusk assemblage. This subzone registers an inverse correlation between Nothofagus dombeyi type and Echinidinium-Islandinium complex concentration values during ca. 4160 14C yr B.P. (4736 cal yr B.P.)-4064 14C yr B.P. (4540 cal yr B.P.), suggesting a variable climatic condition, probably related to Neoglacial episodes occurred in the southern Patagonia Andes during this interval. The pollen assemblages permit direct correlations with the onshore palynostratigraphy from southern of Tierra del Fuego. The high percentages of Nothofagus dombeyi type recorded throughout most of the profile strongly suggest the presence of a closed forest, confirming the existence of a variable, cool and wet climate for the Archipiélago Cormoranes area during the Middle-Late Holocene.